Low threshold electron emission from diamond - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1999)
We have studied the photoassisted electron emission of single-crystal diamond (111) for photon energies from just above the diamond band gap of 5.5 eV well into the sub-band-gap regime (hν≈2.8eV). As an independent parameter, the electron affinity was varied between -1.27 eV [negative electron affinity (NEA)] and +0.38 eV [positive electron affinity (PEA)] by changing the hydrogen coverage of the surface. A substantial sub-band-gap emission band with constant intensity is observed in all cases. Except for the NEA surfaces, it dominates the electron flux. We attribute this intense band to nanometer-size graphitic patches which cover less than 1% of the surface area. The low-energy threshold for this emission band is, however, not determined by intrinsic properties of graphite, but controlled by the work function of the surrounding diamond matrix. The details of this inhomogeneous emission model, which may have implications for the field emission from nanocrystalline diamond films, are discussed. ©1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.lowthr